Dynamical asymmetries in idiopathic scoliosis during forward and lateral initiation step - Bruyneel, Anne-Violette (Springer-Verlag, 2009)
Adolescent idiopathic scoliosis (AIS) is characterized by morphological trunk modifications acting on body mass distribution. Some specific biomechanical strategies during postural regulation have been reported. Given that spinal deformity is three-dimensional, some strategy analysis resulting from different stepping directions should lead to a better understanding of the dynamic adaptation of behaviour. The aim of this study is to identify dynamic strategies of AIS patients stepping in lateral and forward directions. Ten AIS patients with a right thoracic curve and 15 controlled volunteers have been tested. Ground reaction forces (GRF) have been recorded for right-limb stepping and for left-limb stepping associated to forward and lateral directions. Force amplitudes, corresponding occurrences, impulses of stepping phases and an asymmetry index have been computed. Asymmetry and variability increased in the AIS group, compared to the control group, whatever the stepping direction is. Asymmetry for AIS patients systematically provides an increased left initiation GRF compared to a right initiation. Nevertheless, for both groups, lateral initiation shows the largest asymmetry index reported for a forward initiation. More precisely, adaptive dynamic strategies for the AIS group have been characterized by an asymmetry between right and left limbs for lateral and forward initiation. These results can be explained by the influence of scoliosis pathology on dynamic movements due to spinal deformity. A right thoracic curve leads to an extra weight on the limb, which needs to be moved; consequently, stepping initiation with the right limb was more challenging for patients than stepping with the left limb. For the AIS group, the observed variability can also depend on the ontogenesis of adaptive strategies. Lateral step initiation has to be considered as the most relevant paradigm to study scoliosis and may also serve as a clinical basis for treatment to analyse the dynamic postural control and asymmetry strategies of the scoliosis patient.